Magel2 truncation alters select behavioral and physiological outcomes in a rat model of Schaaf-Yang syndrome - Reznik, Derek; Yang, Mingxiao V.; Albelda de la Haza, Pedro; Jain, Antrix; Spanjaard, Melanie; Theiß, Susanne; Schaaf, Christian P.; Malovannaya, Anna; Strong, Theresa V.; Veeraragavan, Surabi; Samaco, Rodney C. (Disease models & mechanisms, 2023)
Previous studies in mice have utilized Magel2 gene deletion models to examine the consequences of its absence. We report the generation, molecular validation and phenotypic characterization of a novel rat model with a truncating Magel2 mutation modeling variants associated with Schaaf-Yang syndrome-causing mutations. ...
Online veröffentlicht am 3. Februar 2023
Gesehen am 05.12.2023